Neu1 deficiency and fibrotic lymph node microenvironment lead to imbalance in M1/M2 macrophage polarization - Escalona, Emilia; Olate-Briones, Alexandra; Albornoz-Muñoz, Sofía; Bonacic-Doric, Enzo; Rodríguez-Arriaza, Francisca; Herrada, Andrés A.; Escobedo, Noelia (Frontiers in Immunology, 2024)
Macrophages play a pivotal role in tissue homeostasis, pathogen defense, and inflammation resolution.M1 and M2 macrophage phenotypes represent two faces in a spectrum of responses to microenvironmental changes, crucial in both physiological and pathological conditions.Neuraminidase 1 (Neu1), a lysosomal and cell surface sialidase responsible for removing terminal sialic acid residues from glycoconjugates, modulates several macrophage functions, including phagocytosis and Toll-like receptor (TLR) signaling. Current evidence suggests that Neu1 expression influences M1/M2 macrophage phenotype alterations in the context of cardiovascular diseases, indicating a potential role for Neu1 in macrophage polarization. For this reason, we investigated the impact of Neu1 deficiency on macrophage polarization in vitro and in vivo. Using bone marrow-derived macrophages (BMDMs) and peritoneal macrophages from Neu1 knockout (Neu1 -/-) mice and wildtype (WT) littermate controls, we demonstrated that Neu1-deficient macrophages exhibit an aberrant M2-like phenotype, characterized by elevated macrophage mannose receptor 1 (MMR/CD206) expression and reduced responsiveness to M1 stimuli. This M2-like phenotype was also observed in vivo in peritoneal and splenic macrophages. However, lymph node (LN) macrophages from Neu1 -/- mice exhibited phenotypic alterations with reduced CD206 expression. Further analysis revealed that peripheral LNs from Neu1 -/-mice were highly fibrotic, with overexpression of transforming growth factor-beta 1 (TGF-β1) and hyperactivated TGF-β signaling in LN macrophages. Consistently, TGF-β1 was found to alter M1/M2 macrophage polarization in vitro. Our findings showed that Neu1 deficiency prompts macrophages towards an M2 phenotype and that microenvironmental changes, particularly increased TGF-β1 in fibrotic tissues such as peripheral LNs in Neu1 -/-mice, further influence M1/M2 macrophage polarization, highlighting its sensitivity to the local microenvironment. Therapeutic interventions targeting Neu1 or TGF-β signaling pathways may offer the potential to regulate macrophage behavior across different diseases.